Pressmud: A potential ameliorant for greening the sodic lands - Sheoran, Parvender; Raju, R.; Prajapat, Kailash; Kumar, Arvind; Barman, Arijit; Sharma, P. C.; Chahal, V. P (Indian Farming, 2019)
Continuous use of bicarbonate dominated residual alkalinity in irrigation water results in build-up of excessive salt concentration (Na+) and soil sodicity (soil pH>8.5). This process adversely affects the plant growth and soil physico-chemical properties consequently impacting crop yields. Mined gypsum (CaSO4.2H2O) is the most preferred ameliorant in sodic areas where farmers use it to reclaim and manage their lands owing to comparatively lower price due to provision of government subsidy, ease in application as compared to other chemical amendments. However, the gypsum production/availability is limited to 6-7 million tonnes/year in India (by-product gypsum and natural gypsum) from all available resources. To reclaim huge chunk of ever increasing sodic soils (caused by anthropogenic and natural process), the sole dependence on gypsum for reclamation purpose seems to be over-burdened enforcing the farmers to look forward for other alternatives.